Does religion influence the labour supply of married women in Germany? - Guido Heineck (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
On behavioural theory basis, this article analyses whether religion influences married women in Germany in their decision to supply labour. Gender roles and accompanying attitudes toward the appropriate division of labour among spouses might differ across religious groups depending on the groups strictness. Using data from the German Socio-Economic Panel (GSOEP) and applying both cross-sectional and longitudinal data analysis techniques the findings from the estimated reduced form participation equations suggest that denominational affiliation itself only weakly influences a womans decision whether to work or not. However, women who attach importance to faith in their lives tend to work less than women without a strong conviction. Furthermore, taking into account the family background of individuals and supposing that employment decisions are bargained over among household members, there is evidence that the existence of a spouse with a strong conviction also affects a womans supply of labour negatively.
Keywords: J22; Z12; 330; Female labour supply; religious attitudes; Frauenerwerbstätigkeit; Arbeitsangebot; Religion; Soziale Rolle; Geschlecht; Deutschland